Optimalisasi Pemasaran Digital Sirup Jeruk Terusan melalui Pelatihan Manajemen Modern dan Integrasi Website-WhatsApp API - Rizki, Fido; Wisdalia Maya Sari; Nasruddin; Bima Ilmawan; Juli Wiwinsih (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service activity targets a home industry known as Rumah Produksi Sirup Jeruk Terusan, located in Desa Terusan, Musi Rawas Utara Regency, which serves as a center for citrus cultivation. The primary issues faced by the partner include limited understanding of modern management, especially in financial management, business planning, and human resource management; underutilization of digital marketing; and challenges related to access and management of digital technology. The objectives of this activity were to enhance the managerial skills of the partner through modern management practices, optimize the use of digital marketing technologies such as social media, websites, and WhatsApp API integration, and strengthen the competitiveness of local products in broader markets. The implementation method consisted of systematic stages: socialization, training, technology application, mentoring, evaluation, and program sustainability efforts. The results of the activity showed a significant improvement in the managerial capacity of the partner. Based on the pretest and posttest evaluations, the recap indicated a considerable increase. The average improvement in managerial skills after participating in the series of training and mentoring activities reached 35.3%. This improvement confirms that the implemented program successfully delivered a tangible impact on enhancing the partner’s knowledge and skills in applying modern management practices.. Furthermore, the partner successfully developed an active e-commerce website integrated with a WhatsApp API Gateway system to facilitate swift and efficient communication and product ordering. The website is accessible at https://siruplimau-desaterusan.com/. The adoption of this digital platform is expected to drive the expansion of Sirup Jeruk Terusan's market reach and enhance business professionalism. This activity confirms that integrating modern management with digital technology can effectively improve marketing efficiency and the competitiveness of MSME products. Future development is recommended to focus on strengthening human resource capacity and expanding integration with other e-commerce platforms to increase market penetration.